The writing performance of undergraduates in the University of Technology Mara, Terengganu, Malaysia - Awg Nik, Yah; Sani, Badariah; Wan Chik, Muhmad Noor; Jusoff, Kamaruzaman; Hasbollah, Hasif Rafidee (Academic Journals, 2010)
Writing well and effectively helps our students achieve three important objectives. Firstly, it reinforces grammatical structures, idioms and vocabulary. Secondly, writing provides opportunities for our students to be more adventurous with the language, to go beyond what they have learnt and to take risks with the effects of writing. And, finally, the importance of writing lies in the ability to develop language skills in terms of fluency, accuracy and appropriateness, in the communication of meanings and messages. This paper attempts to investigate a comparative study on the undergraduates’ writing performance and the problems that hinder students’ perception of good writing skills. As English Language is used in all the subjects taught in their degree performance, these students should acquire and also achieve some kind of satisfactory level of writing proficiency. Lecturers expect them to use and write daily tasks, assignments and answer examination questions using English proficiently and effectively. In this study, the students from the Diploma Programme acquired better writing skills than the Matriculation students. The Diploma students performed better in all the five writing components like content, vocabulary, organization, language use and mechanics. This was because the Diploma students had more exposure in English as all the subjects were taught in English Language. Therefore, the Matriculation students were slightly less proficient in their writing performance compared with the Diploma students. Nevertheless, the component like mechanics in writing did not contribute greatly to their writing proficiency and both groups of students scored almost the same percentage. The most significant component in writing that hindered their writing proficiency was language use. Both the Diploma and Matriculation students scored very low percentage in this component. Firstly, because ESL students faced more problems than the first language students as they have to acquire or consciously learn the grammar, syntactic structure, vocabulary, rhetorical structure and idioms of a new language. Secondly, composing and writing is already a difficult task for them and the acquisition of grammar and other language structures make it even more difficult. Finally, students who do not read and write well in their first language need to work harder on the new creative activity of forming ideas and thoughts in English for the readers to understand. Therefore, it is recommended that writing lecturers to provide our students ample time and opportunities for them to write and form ideas clearly. Next, choosing topics for students to write with care can also nurture the development of composing abilities. It can be concluded that lecturers should focus on helping students to become aware of how and why they write, and on encouraging them to write freely, fluently and well.